Method for recycling titanium in titanium white waste acid
By adding aluminum hydroxide to titanium dip acid, and then adding phosphate, aluminum salt flocculants are used to condense titanium titanium particles, which solves the problem of fineness and viscosity of titanium picillosol in titanium white waste acid, and realizes titanium phosphate. Effective recovery and improvement of product whiteness have reduced production costs.
Patent Information
- Application Number
- CN202411533674.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-30
- Publication Date
- 2025-01-24
AI Technical Summary
In the prior art, the titanium phosphate particles in titanium dioxide waste acid are too fine and have a large viscosity, which leads to difficulty in suction filtration and water washing, and cannot be directly used for titanium dioxide production. In addition, conventional alkali treatment methods will reduce product whiteness and increase production costs.
By adding aluminum hydroxide in titanium dioxide, then add phosphate, and use the generated aluminum salt as a flocculant to condense the small particles of titanium phosphate, increase the size of the particles, reduce viscosity, facilitate filtration and water washing, and get rid of water. Titanium phosphate is directly used in titanium pink production.
It effectively solves the problems of too fine particles and high viscosity of titanium phosphate. Impurities are removed by washing with water, and the obtained titanium phosphate can be directly reused in the production of titanium dioxide, which improves the whiteness of the product, reduces production costs, and does not require the addition of additional salt treatment agents. , avoiding the generation of ammonia nitrogen wastewater.
Smart Images

Figure BDA0005111364830000111 
Figure BDA0005111364830000121
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of titanium dioxide production, and in particular to a method for recovering titanium in titanium dioxide waste acid. Background Art
[0002] The scientific name of titanium dioxide is titanium dioxide. It is widely used in coatings, plastics, papermaking, inks and other fields due to its excellent whiteness, hiding power, weather resistance and chemical stability. At present, the production processes of titanium dioxide mainly include sulfuric acid method and chlorination method. Titanium dioxide waste acid is produced during the production process, and titanium dioxide waste acid usually contains some titanium. For example, the titanium dioxide waste acid produced by sulfuric acid method contains unhydrolyzed titanium oxysulfate. How to recycle the titanium in titanium dioxide waste acid is an important issue that needs to be solved in the titanium dioxide production process.
[0003] At present, the main method for extracting titanium from waste acid of titanium dioxide is to use phosphoric acid to form titanium phosphate precipitation. However, due to the high content of impurities (iron, magnesium, calcium, aluminum, etc.) in the waste acid, it is necessary to wash it with water to remove them, and the obtained pure titanium phosphate is reused in production or sold as a product. However, due to the excessively fine particles and high viscosity of titanium phosphate during the generation process, it is difficult to filter and wash it with water. The impurity content of titanium phosphate is high, and it cannot be reused in titanium dioxide production by simple washing.
[0004] The patent application with announcement number CN115231540A discloses a method for preparing titanium phosphate from waste acid produced as a by-product of titanium dioxide production by the chlorination process. Titanium phosphate colloid is synthesized using waste acid from titanium dioxide produced by the chlorination process and dilute phosphoric acid as raw materials, and the titanium phosphate product is prepared through processes such as filtration, pickling, bleaching, drying, and calcination. The process is simple to operate, but the titanium phosphate colloid has fine particles and high viscosity, and is difficult to settle and wash, making it difficult to implement industrially.
[0005] The patent application with the announcement number CN107686126A discloses a method for reducing the viscosity of the alkali-soluble metatitanic acid slurry. By using carbonate, hydroxide or ammonia water for alkali neutralization and washing of metatitanic acid, the viscosity of the conventional alkali-soluble metatitanic acid slurry is reduced. The high viscosity of the metatitanic acid mentioned in the patent is mainly due to the increase in viscosity caused by the high slurry concentration, which is different from the viscosity caused by the excessively fine titanium phosphate particles. The alkaline substance used in this method contains sodium ions or ammonia water. The sodium ions introduced into the material cannot be completely removed during the water washing stage, which will make the color of the kiln products yellowish, affecting the product quality. Neutralization with ammonia water will cause the ammonia nitrogen content in the later washing water to exceed the standard, increasing the cost of sewage treatment. In addition, this method also needs to add a salt treatment agent during the salt treatment process, which is costly, and simple physical mixing can only attach the salt treatment agent to the surface of the metatitanic acid, and cannot be dispersed into the microscopic particles to achieve the purpose of uniform dispersion, thereby weakening the role of the salt treatment agent in the calcination process, affecting the product quality, and the salt treatment agent will be lost with the filter press water during the pre-kiln filter press process, and the retention rate is low.
[0006] In view of this, the present invention is proposed. Summary of the invention
[0007] The purpose of the present invention is to provide a method for recycling titanium in titanium dioxide waste acid, so as to solve the technical problems that the titanium phosphate particles generated by the reaction of titanium dioxide waste acid with phosphoric acid in the prior art are too fine, have high viscosity, are difficult to filtrate and wash, and cannot be directly reused in titanium dioxide production by simple washing, as well as the technical problems that the product obtained by conventional alkali treatment to reduce viscosity has low whiteness and high treatment cost. The method of the present invention sequentially adds aluminum hydroxide and phosphoric acid to titanium dioxide waste acid, and uses the generated aluminum salt as a flocculant to condense small titanium phosphate particles, increase the particle size, reduce viscosity, and facilitate subsequent filtration and washing. The titanium phosphate after washing and impurity removal can be directly reused in the salt treatment process of the sulfuric acid method titanium dioxide production process, so that the titanium in the waste acid is effectively recovered; and the obtained product has high whiteness, no ammonia nitrogen wastewater is generated, and no salt treatment agent needs to be added in the subsequent salt treatment process, and the production cost is low.
[0008] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:
[0009] A method for recycling titanium in titanium dioxide waste acid comprises the following steps:
[0010] S1. After heating the titanium dioxide waste acid, add Al(OH) 3 and phosphoric acid, allowing to stand after the reaction, removing the supernatant, and obtaining titanium phosphate solid;
[0011] S2. bleaching and washing the titanium phosphate solid to obtain titanium phosphate after impurity removal;
[0012] S3. adding the impurity-removed titanium phosphate to the slurry before the sulfuric acid titanium dioxide salt treatment, recovering the titanium therein, and obtaining the kiln product through salt treatment and calcination.
[0013] Preferably, the titanium dioxide waste acid includes sulfuric acid titanium dioxide waste acid and / or chloride process titanium dioxide waste acid.
[0014] Preferably, the TiO in the titanium dioxide waste acid 2 The content is 4-9g / L.
[0015] Preferably, in step S1, the temperature after heating is 60-90°C.
[0016] Preferably, in step S1, the Al(OH) 3 The amount of Al(OH) added is controlled according to the end point pH. 3 The pH of the post-feed liquid is 1-3.
[0017] Preferably, in step S1, the Al(OH)3 After that, the phosphoric acid is added after stirring and dispersing for 10-50 minutes.
[0018] Preferably, in step S1, the amount of phosphoric acid added is: 3 PO 4 :TiO 2 =1.35-1.75 measurement.
[0019] Preferably, in step S1, after adding the phosphoric acid, the reaction time is 10-50 min.
[0020] Preferably, in step S1, the standing time is 0.5-2h.
[0021] Preferably, in step S3, the amount of titanium phosphate added after impurity removal is based on the Al content of the kiln product. 2 O 3 The content of Al in the kiln product is controlled. 2 O 3 The mass percentage is 0.2%-0.3%.
[0022] Compared with the prior art, the present invention has the following beneficial effects:
[0023] (1) The method of the present invention adds aluminum hydroxide before adding phosphoric acid, which can effectively solve the problem that the generated titanium phosphate is too fine and has a high viscosity, making it difficult to filter and wash. The impurities in the titanium phosphate solid can be effectively removed by bleaching and washing. The titanium phosphate after washing and impurity removal can be directly reused in the salt treatment process of sulfuric acid titanium dioxide production, effectively recovering the titanium in the titanium dioxide waste acid, and the phosphate and aluminum ions can be reused in production as salt treatment agents. There is no need to add additional salt treatment agents during the salt treatment process, avoiding the introduction of other impurities, significantly reducing the amount of salt treatment agents used, and saving production costs.
[0024] (2) In the method of the present invention, phosphorus and aluminum can be dispersed inside the titanate particles, which can effectively increase the retention rate of aluminum ions compared with the traditional salt treatment process, enhance the effect of the phosphate aluminum salt treatment agent on improving the crystal form, and improve the performance indicators of the kiln products.
[0025] (3) The method of the present invention is simple and effective, and the reaction conditions are mild and controllable, and is suitable for workshop-scale production. DETAILED DESCRIPTION
[0026] The technical scheme of the present invention will be clearly and completely described below in conjunction with specific embodiments, but it will be appreciated by those skilled in the art that the following described embodiments are part of embodiments of the present invention, rather than all embodiments, and are only used to illustrate the present invention, and should not be considered as limiting the scope of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work, all belong to the scope of protection of the present invention. If specific conditions are not indicated in the embodiments, they are carried out according to normal conditions or conditions recommended by the manufacturer. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0027] The present invention provides a method for recycling titanium in titanium dioxide waste acid, comprising the following steps:
[0028] S1. After heating the titanium dioxide waste acid, add Al(OH) 3 and phosphoric acid, allowing to stand after the reaction, removing the supernatant, and obtaining titanium phosphate solid;
[0029] S2. Bleaching and washing the titanium phosphate solid obtained in step S1 to obtain titanium phosphate after impurity removal;
[0030] S3. Add the impurity-removed titanium phosphate to the slurry before the sulfuric acid titanium dioxide salt treatment, recover the titanium therein, and obtain the kiln product after salt treatment and calcination.
[0031] According to the method of the present invention, aluminum hydroxide is first added before phosphoric acid is added to neutralize part of hydrogen ions. The generated aluminum salt can be used as a flocculant. Aluminum oxide colloid generated by aluminum ion ionization is evenly distributed in the solution. Phosphoric acid is then added to react to generate titanium phosphate. The aluminum hydroxide colloid causes small titanium phosphate particles to condense, and increasing the particle size is beneficial to subsequent filtration and water washing. The generated titanium phosphate can be washed to remove impurity ions therein to obtain pure titanium phosphate. The titanium phosphate after water washing and impurity removal can be directly reused in the salt treatment process of sulfuric acid process titanium dioxide production, thereby realizing effective recovery and utilization of titanium. In addition, during the salt treatment process, the phosphate and aluminum ions in titanium phosphate can be used as salt treatment agents without the introduction of other impurity elements, and the amount of salt treatment agent added can be reduced, saving costs; and, in the method of the present invention, the titanium phosphate generated in the process of first adding aluminum hydroxide to generate an aluminum salt flocculant and then adding phosphoric acid will wrap the aluminum salt to form a titanium-phosphorus-aluminum uniform mixture, which is uniformly mixed with titanic acid during the salt treatment stirring process, achieving the effect of dispersing the salt treatment ions inside the titanic acid, effectively enhancing the effect of the phosphate aluminum salt treatment agent on improving the crystal form in the calcination stage, optimizing the crystal size and distribution of the kiln product, and improving the performance indicators of the product.
[0032] Conventional alkali (such as sodium hydroxide, ammonia water) treatment can also make titanium phosphate precipitate and achieve water washing, but it will reduce product quality and / or increase production costs. The principle of conventional alkali treatment to precipitate titanium phosphate is mainly to reduce the acid radicals on the surface of titanium phosphate, reduce the surface charge, and reduce the repulsion between particles, thereby achieving precipitation. However, the sodium ions introduced into the material cannot be completely removed during the water washing stage, which will make the color of the kiln products yellowish and reduce the whiteness, affecting product quality; and ammonia water neutralization will cause the ammonia nitrogen content in the later washing water to exceed the standard, increasing the cost of sewage treatment; at the same time, the titanium phosphate obtained by sodium hydroxide or ammonia water treatment does not contain salt treatment agent, and after being reused in the salt treatment process, additional salt treatment agent needs to be added, and the amount of salt treatment agent is large, and the production cost is high. The method of the present invention can overcome the above-mentioned defects. It can not only precipitate the generated titanium phosphate and return it to production after washing and removing impurities, but also will not affect the product quality. The obtained kiln product has high whiteness and does not generate ammonia nitrogen wastewater. After being returned to the salt treatment process, there is no need to add additional salt treatment agent. The production cost is low, and the salt treatment agent can be dispersed inside the metatitanic acid to improve the performance of the product.
[0033] In some specific embodiments of the present invention, the titanium dioxide waste acid used includes sulfuric acid titanium dioxide waste acid and / or chloride titanium dioxide waste acid.
[0034] In some specific embodiments of the present invention, the TiO 2 The content is 4-9g / L, for example, it can be any point value among 4g / L, 4.3g / L, 4.8g / L, 5g / L, 5.2g / L, 5.6g / L, 6g / L, 6.5g / L, 7g / L, 7.5g / L, 8g / L, 8.6g / L, 9g / L or a range value consisting of any two point values.
[0035] In some specific embodiments of the present invention, in step S1, the temperature of the titanium dioxide waste acid after heating is 60-90°C, for example, it can be any point value among 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C or a range value consisting of any two point values.
[0036] In some specific embodiments of the present invention, in step S1, Al(OH) 3 The amount of addition is controlled according to the end point pH. Add Al(OH) 3 The pH of the subsequent liquid is 1-3. For example, after adding aluminum hydroxide, the pH of the liquid can be any value among 1, 1.5, 2, 2.5, 3, or a range consisting of any two values.
[0037] In some specific embodiments of the present invention, in step S1, Al(OH) is added 3 After that, add phosphoric acid after stirring and dispersing for 10-50 minutes, in order to make Al(OH) 3The reaction is sufficient and the generated aluminum salt is evenly dispersed; for example, the stirring and dispersing time can be any point value among 10min, 15min, 20min, 25min, 30min, 35min, 40min, 45min, 50min or a range value consisting of any two point values.
[0038] In some specific embodiments of the present invention, in step S1, the amount of phosphoric acid added is in molar ratio H 3 PO 4 :TiO 2 =1.35-1.75 measurement, for example H 3 PO 4 and TiO 2 The molar ratio can be any value among 1.35, 1.4, 1.45, 1.5, 1.55, 1.6, 1.65, 1.7, 1.75 or a range value consisting of any two values.
[0039] In some specific embodiments of the present invention, in step S1, after adding phosphoric acid, the reaction time is 10-50 min, for example, it can be any point value among 10 min, 20 min, 30 min, 40 min, 50 min or a range value consisting of any two point values.
[0040] In some specific embodiments of the present invention, in step S1, after the reaction is completed, the standing time is 0.5-2h, for example, it can be any point value among 0.5h, 1h, 1.5h, 2h or a range value consisting of any two point values.
[0041] In some specific embodiments of the present invention, in step S3, the amount of titanium phosphate added during recycling after impurity removal is based on the Al content in the kiln product. 2 O 3 The content of Al in the kiln product is controlled. 2 O 3 The mass percentage is 0.2%-0.3%, for example, it can be any point value among 0.2%, 0.22%, 0.24%, 0.26%, 0.28%, 0.3% or a range value consisting of any two point values.
[0042] In some specific embodiments of the present invention, between steps S2 and S3, there is also a step of calcining a small sample of the titanium phosphate after impurities are removed and performing elemental analysis on it, in order to obtain the contents of phosphorus and aluminum so as to determine the amount of the titanium phosphate to be added during recycling after impurities are removed.
[0043] The following is a detailed description of some embodiments of the present invention in conjunction with specific examples. The raw materials used in the examples can be purchased from the market unless otherwise specified.
[0044] Example 1
[0045] S1. Take the waste acid (TiO 2 The content is 4.97g / L), the temperature is raised to 90°C under stirring, and Al(OH) is added after the temperature stabilizes. 3 After stirring for 20 min until the pH reaches 1, add phosphoric acid (molar ratio H 3 PO 4 :TiO 2 =1.35), after stirring and reacting for 10 min, stirring and heating were stopped, and the mixture was allowed to stand for 1 h. The supernatant was removed to obtain titanium phosphate solid;
[0046] S2. Bleaching and washing the titanium phosphate solid obtained in step S1 to obtain the impurity-free titanium phosphate;
[0047] S3. Take a small sample of titanium iron phosphate after impurities are removed, calcine at 500℃ and determine the elemental analysis to obtain P 2 O 5 / TiO 2 Molar ratio and Al 2 O 3 / TiO 2 The molar ratios were 1.33 and 3.1 respectively. The remaining material was then slurried to determine the total titanium content of 4.93 g / L. The phosphorus content (P 2 O 5 ) and aluminum content (in Al 2 O 3 Calculate), and add it to the slurry before the sulfuric acid titanium dioxide salt treatment in proportion to make the Al content of the kiln product 2 O 3 The mass percentage is 0.26%-0.28%, and the titanium therein is recycled; the metatitanic acid treated with salt is calcined to obtain the kiln product, and the material indicators are measured to meet the production indicators, and the blue light whiteness is 92.6.
[0048] Example 2
[0049] S1. Take the waste acid (TiO 2 The content is 5.2g / L), the temperature is raised to 60℃ under stirring, and Al(OH) is added after the temperature stabilizes. 3 After stirring for 10 min until the pH reaches 3, add phosphoric acid (molar ratio H 3 PO 4 :TiO 2 =1.35), after stirring and reacting for 20 min, stirring and heating were stopped, and the mixture was allowed to stand for 0.5 h, and the supernatant was removed to obtain titanium phosphate solid;
[0050] S2. Bleaching and washing the titanium phosphate solid obtained in step S1 to obtain the impurity-free titanium phosphate;
[0051] S3. Take a small sample of titanium phosphate after impurities are removed, calcine at 500℃ and measure the elemental analysis to obtain P 2 O 5 / TiO 2 Molar ratio and Al 2 O 3 / TiO 2 The molar ratios were 1.33 and 3.54 respectively. The remaining material was then slurried to determine the total titanium content of 5.1 g / L. The phosphorus content (P 2 O 5 ) and aluminum content (in Al 2 O 3 Calculate), and add it to the slurry before the sulfuric acid titanium dioxide salt treatment in proportion to make the Al content of the kiln product 2 O 3 The mass percentage is 0.26%-0.28%, and the titanium therein is recycled; the metatitanic acid treated with salt is calcined to obtain the kiln product, and the material indicators are measured to meet the production indicators, and the blue light whiteness is 92.7.
[0052] Example 3
[0053] S1. Take the waste acid (TiO 2 The content is 8.62g / L), the temperature is raised to 75℃ under stirring, and Al(OH) is added after the temperature stabilizes. 3 After stirring for 35 min, add phosphoric acid (molar ratio H 3 PO 4 :TiO 2 =1.6), after stirring and reacting for 40 min, stirring and heating were stopped, and the mixture was allowed to stand for 1.5 h, and the supernatant was removed to obtain titanium phosphate solid;
[0054] S2. Bleaching and washing the titanium phosphate solid obtained in step S1 to obtain the impurity-free titanium phosphate;
[0055] S3. Take a small sample of titanium phosphate after impurities are removed, calcine at 500℃ and measure the elemental analysis to obtain P 2 O 5 / TiO 2 Molar ratio and Al 2 O 3 / TiO 2 The molar ratios were 1.33 and 3.36 respectively. The remaining material was then slurried to determine the total titanium content of 8.54 g / L. The phosphorus content (P 2 O 5 ) and aluminum content (in Al2 O 3 Calculate), and add it to the slurry before the sulfuric acid titanium dioxide salt treatment in proportion to make the Al content of the kiln product 2 O 3 The mass percentage is 0.26%-0.28%, and the titanium therein is recycled; the metatitanic acid treated with salt is calcined to obtain the kiln product, and the material indicators are measured to meet the production indicators, and the blue light whiteness is 92.5.
[0056] Example 4
[0057] S1. Take the waste acid (TiO 2 The content is 6.51g / L), the temperature is raised to 80℃ under stirring, and Al(OH) is added after the temperature stabilizes. 3 After stirring for 50 min until the pH reaches 2, add phosphoric acid (molar ratio H 3 PO 4 :TiO 2 =1.5), after stirring and reacting for 30 min, stirring and heating were stopped, and the mixture was allowed to stand for 1 h. The supernatant was removed to obtain titanium phosphate solid;
[0058] S2. Bleaching and washing the titanium phosphate solid obtained in step S1 to obtain the impurity-free titanium phosphate;
[0059] S3. Take a small sample of titanium phosphate after impurities are removed, calcine at 500℃ and measure the elemental analysis to obtain P 2 O 5 / TiO 2 Molar ratio and Al 2 O 3 / TiO 2 The molar ratios were 1.33 and 3.2 respectively. The remaining material was then slurried to determine the total titanium content of 6.3 g / L. The phosphorus content (P 2 O 5 ) and aluminum content (in Al 2 O 3 Calculate), and add it to the slurry before the sulfuric acid titanium dioxide salt treatment in proportion to make the Al content of the kiln product 2 O 3 The mass percentage is 0.26%-0.28%, and the titanium therein is recycled; the metatitanic acid treated with salt is calcined to obtain the kiln product, and the material indicators are measured to meet the production indicators, and the blue light whiteness is 92.3.
[0060] Example 5
[0061] S1. Take the waste acid (TiO 2 The content is 4.3g / L), the temperature is raised to 70℃ under stirring, and Al(OH) is added after the temperature stabilizes.3 After stirring and dispersing for 40 min, phosphoric acid (molar ratio H 3 PO 4 :TiO 2 =1.75), react with stirring for 50 min, stop stirring and heating, let stand for 2 h, and pour off the supernatant to obtain titanium phosphate solid;
[0062] S2. Bleaching and washing the titanium phosphate solid obtained in step S1 to obtain the impurity-free titanium phosphate;
[0063] S3. Take a small sample of titanium phosphate after impurities are removed, calcine at 500℃ and measure the elemental analysis to obtain P 2 O 5 / TiO 2 Molar ratio and Al 2 O 3 / TiO 2 The molar ratios were 1.33 and 3.17 respectively. The remaining material was then slurried to determine the total titanium content of 4 g / L. The phosphorus content (P 2 O 5 ) and aluminum content (in Al 2 O 3 Calculate), and add it to the slurry before the sulfuric acid titanium dioxide salt treatment in proportion to make the Al content of the kiln product 2 O 3 The mass percentage is 0.26%-0.28%, and the titanium therein is recycled; the metatitanic acid treated with salt is calcined to obtain the kiln product, and the material indicators are measured to meet the production indicators, and the blue light whiteness is 92.4.
[0064] Comparative Example 1
[0065] S1. Take the waste acid (TiO 2 The content was 4.3 g / L), the temperature was raised to 70°C under stirring, and phosphoric acid (molar ratio H 3 PO 4 :TiO 2 =1.75), after stirring and reacting for 50 min, stirring and heating were stopped, NaOH was added until flocculent precipitation was complete, and then it was allowed to stand for 2 h, and the supernatant was poured off to obtain titanium phosphate solid;
[0066] S2. Bleaching and washing the titanium phosphate solid obtained in step S1 to obtain the impurity-free titanium phosphate;
[0067] S3. Take a small sample of titanium phosphate after impurities are removed, calcine at 500℃ and measure the elemental analysis to obtain P 2 O 5 / TiO 2The molar ratio is 1.33, and then the remaining material is slurried to determine the total titanium content of 4g / L, and the phosphorus content (P 2 O 5 ), and added to the slurry before the sulfuric acid titanium dioxide salt treatment (the addition ratio is the same as in Example 5), the titanium therein is recovered and utilized, and then TiO 2 4% aluminum sulfate in the total amount to ensure that the Al content of the kiln products is 2 O 3 The content is the same as in Example 5 (0.26-0.28%);
[0068] The salt-treated metatitanic acid was calcined to obtain the kiln product. The material indicators were measured and the blue light whiteness was 89.7.
[0069] Comparative Example 2
[0070] S1. Take the waste acid (TiO 2 The content was 4.3 g / L), the temperature was raised to 70°C under stirring, and phosphoric acid (molar ratio H 3 PO 4 :TiO 2 =1.75), after stirring and reacting for 50 min, stirring and heating were stopped, ammonia water was added until flocculent precipitation was complete, and then the mixture was allowed to stand for 2 h, and the supernatant was removed to obtain titanium phosphate solid;
[0071] S2. Bleaching and washing the titanium phosphate solid obtained in step S1 to obtain the impurity-free titanium phosphate;
[0072] S3. Take a small sample of titanium phosphate after impurities are removed, calcine at 500℃ and measure the elemental analysis to obtain P 2 O 5 / TiO 2 The molar ratio is 1.33, and then the remaining material is slurried to determine the total titanium content of 4g / L, and the phosphorus content (P 2 O 5 ), and added to the slurry before the sulfuric acid titanium dioxide salt treatment (the addition ratio is the same as in Example 5), the titanium therein is recovered and utilized, and then TiO 2 4% aluminum sulfate in the total amount to ensure that the Al content of the kiln products is 2 O 3 The content is the same as in Example 5 (0.26-0.28%);
[0073] The salt-treated metatitanic acid was calcined to obtain the kiln product. The material indicators met the production indicators and the blue light whiteness was 91.2.
[0074] Comparative Example 3
[0075] Comparative Example 3 is similar to Example 5, except that in step S1, no Al(OH) was added. 3 , phosphoric acid is directly added to the heated waste acid, and the other conditions are the same as those in Example 5.
[0076] However, in the subsequent experiments, it was found that the generated titanium phosphate was in a gel state. After standing for 8 hours, no obvious sedimentation was observed. It was impossible to obtain a thick slurry by pouring off the supernatant, and it was also difficult to wash with water by filtration, so the bleaching and washing experiments could not be carried out. The total titanium content of the obtained titanium phosphate was determined to be 4.1 g / L. The phosphorus content (P 2 O 5 ), and added to the slurry before the sulfuric acid titanium dioxide salt treatment (the addition ratio is the same as in Example 5), the titanium therein is recovered and utilized, and then TiO 2 4% aluminum sulfate in the total amount to ensure that the Al content of the kiln products is 2 O 3 The content is the same as that in Example 5 (0.26-0.28%); the salt-treated metatitanic acid is calcined to obtain a kiln product, and the material indicators are measured. Due to the high impurity content, the blue light whiteness is significantly reduced to only 86.
[0077] Test example
[0078] The iron content of the titanium phosphate after impurity removal obtained in each embodiment and each comparative example was tested, and the test results are shown in Table 1.
[0079] Table 1
[0080] Example Fe content Example 1 11 Example 2 10 Example 3 12 Example 4 11 Example 5 13 Comparative Example 1 11 Comparative Example 2 12 Comparative Example 3 26
[0081] The indices of the kiln products in each embodiment and each comparative example were tested, and the results of the calcination parameters and the kiln product indices are shown in Table 2.
[0082] Table 2
[0083]
[0084]
[0085] From the data in the table, it can be seen that the use of NaOH and ammonia water can also improve the viscosity of the material generated by titanium phosphate, but TiO 24% by weight of aluminum sulfate treatment agent increases production costs; because sodium ions have the effect of promoting rutile conversion, the comparative example 1 in which NaOH is added shortens the holding time at 960°C by 5 minutes, and the CS (crystal size) and CSD (crystal size distribution) of the material also increase. In addition, sodium ions will cause the material to be yellowish, which reduces the whiteness of the kiln product to only 89.7; in the comparative example 2 in which ammonia water is added, ammonia water combined with sulfur will cause the desulfurization temperature to decrease, so the holding time of the high-temperature section of the crystal transformation is shortened by 10 minutes, the ammonia nitrogen content in the washing water exceeds the standard, and ammonia nitrogen wastewater is generated, which increases the water treatment cost. Even if a membrane treatment method is used, ammonia nitrogen wastewater with high concentration and high impurity content will be generated; therefore, based on the above data, the method of using NaOH and ammonia water to achieve sedimentation will increase production costs, and the use of the NaOH process will result in a decrease in material indicators.
[0086] In Comparative Example 3 where no alkali was added, since the titanium phosphate particles were too fine and had a high viscosity, filtering and washing with water were difficult, it was difficult to remove Fe by washing with water, the impurity content was high, and the indexes of the prepared kiln product were poor.
[0087] The treatment method of the present invention can improve the material viscosity of the generated titanium phosphate so that it can be directly reused in production through simple water washing, and the subsequent salt treatment process does not require the addition of additional salt treatment agents, no ammonia nitrogen wastewater is generated, the production cost is low, and the indicators of the prepared kiln products meet the production requirements; in addition, the aluminum salt generated in the method of the present invention is wrapped inside the titanium phosphate, which can achieve the effect of dispersing the salt treatment ions inside the metatitanic acid, effectively enhancing the crystal form improvement effect of the phosphate aluminum salt treatment agent in the calcination stage. Compared with Comparative Example 2, the kiln product CS in the embodiment of the present invention is smaller in size and higher in whiteness.
[0088] Although the present invention has been illustrated and described with specific embodiments, it should be appreciated that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Those skilled in the art should understand that the technical solutions described in the above embodiments may be modified, or some or all of the technical features thereof may be replaced by equivalents without departing from the spirit and scope of the present invention. However, these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention. Therefore, this means that all such replacements and modifications within the scope of the present invention are included in the appended claims.
Claims
1. A method for recycling titanium in titanium dioxide waste acid, characterized in that: The following steps are involved: S1. After heating the titanium dioxide waste acid, Al(OH)3 and phosphoric acid were added sequentially under stirring, and the reaction was allowed to stand, and the supernatant was removed to obtain titanium phosphate solid; S2. bleaching and washing the titanium phosphate solid to obtain titanium phosphate after impurity removal; S3. adding the impurity-removed titanium phosphate to the slurry before the sulfuric acid titanium dioxide salt treatment, recovering the titanium therein, and obtaining the kiln product through salt treatment and calcination.
2. The method for recycling titanium in titanium dioxide waste acid according to claim 1, characterized in that: The titanium dioxide waste acid includes sulfuric acid titanium dioxide waste acid and / or chloride process titanium dioxide waste acid.
3. The method for recycling titanium in titanium dioxide waste acid according to claim 1, characterized in that: The TiO2 content in the titanium dioxide waste acid is 4-9 g / L.
4. The method for recycling titanium in titanium dioxide waste acid according to claim 1, characterized in that: In step S1, the temperature after heating is 60-90°C.
5. The method for recycling titanium in titanium dioxide waste acid according to claim 1, characterized in that: In step S1, the amount of Al(OH)3 added is controlled according to the end point pH, and the pH of the feed solution after adding Al(OH)3 is 1-3.
6. The method for recycling titanium in titanium dioxide waste acid according to claim 1, characterized in that: In step S1, after adding the Al(OH)3, stirring and dispersing for 10-50 minutes, the phosphoric acid is added.
7. The method for recycling titanium in titanium dioxide waste acid according to claim 1, characterized in that: In step S1, the amount of phosphoric acid added is measured at a molar ratio of H3PO4:TiO2=1.35-1.
75.
8. The method for recycling titanium in titanium dioxide waste acid according to claim 1, characterized in that: In step S1, after adding the phosphoric acid, the reaction time is 10-50 minutes.
9. The method for recycling titanium in titanium dioxide waste acid according to claim 1, characterized in that: In step S1, the standing time is 0.5-2h.
10. The method for recycling titanium in titanium dioxide waste acid according to claim 1, characterized in that: In step S3, the amount of titanium phosphate added after impurities removal is controlled according to the Al2O3 content in the kiln product, and the mass percentage of Al2O3 in the kiln product is 0.2%-0.3%.
Citation Information
Patent Citations
Method for reducing viscosity of metatitanic acid alkali-soluble slurry
CN107686126A
Method for preparing titanium phosphate from byproduct waste acid generated in production of titanium dioxide by chlorination process
CN115231540A
Cited By
Method for preparing titanium phosphite from low-concentration titanium-containing waste acid
CN120172370A